From Yogācāra to Philosophical Tantra in Kashmir and Tibet - Duckworth, Douglas S. (Sophia, 2018)
This paper outlines a shift in the role of self-awareness from Yogācāra to tantra and connects some of the dots between Yogācāra, Pratyabhijñā, and Buddhist tantric traditions in Tibet. As is the case with Yogācāra, the Pratyabhijñā tradition of Utpaladeva (10th c.) maintains that awareness is self-illuminating and constitutive of objects. Utpaladeva's commentator and influential successor, Abhinavagupta (10th-11th c.), in fact quotes Dharmakīrti's (7th c.) argument from the Pramāṇaviniścaya that objects are necessarily perceived objects (sahopalambhaniyama). That is, everything known is known in consciousness; there is nothing that can be known outside or separate from consciousness. This aspect of Pratyabhijñā thought is shared with Yogācāra. While Utpaladeva drew upon Yogācāra epistemology to formulate a differential construction of objects (via apoha), he departed from this theory to develop a distinctive monistic framework for the interpretation of subjectivity. By appealing to the ultimate reality of a singularly nonconceptual, transcendental subject rather than a plurality of (non)conceptual particulars, Utpaladeva appropriated Dharmakīrti's epistemological model while turning it on its head. That is, Utpaladeva critiqued Dharmakīrti in one context (his external realism) while he is indebted to him in another (his epistemic idealism) to establish the framework for his own absolute idealism, where everything happens in and through the absolute self that is Siva. Utpaladeva extended (or made explicit) the place of self-awareness in Yogācāra to formulate an absolute idealism that is the theoretic foundation for philosophical tantra. In this paper, I will chart a trajectory of this development, from Yogācāra to Pratyabhijñā, and show how a parallel development took place in tantric assimilations of Yogācāra in Tibet.